Efisiensi Virtual Expo Terhadap Ekspor pada Masa Pandemi Covid-19(CV Surya Rotan Furniture) - Merza Setiadani; Relifra (Teewan Journal Solutions, 2024)
The study aims to analyze the marketing efficiency by participating in virtual expo and indentifying obstacles that companies faced during the pandemic in marketing their products and what steps the company is using to cope with those obstacles. The method used in this study in the BEP (Break Even Point) formula approach and the marketing efficiency formulas to analyze the number of units that must be sold annually as well as the marketing efficiency before and durin the pandemic occurs.The result of this study are 2% for 2019, 1.27% for 2020 and 0.16% for 2021. These result mean that the promotion of Surya Rotan Furniture CV’s products by participating in the virtual expo is considered efficient based on marrketing efficiency scale.